Evaluation of Factors Impacting the Efficacy of Single or Combination Therapies of Valproic Acid, Carbamazepine, and Oxcarbazepine: A Longitudinal Observation Study - Peng, Qilin; Ma, Mubai; Gu, Xurui; Hu, Yani; Zhou, Boting (Frontiers in Pharmacology, 2021)
Objective: This study aimed to determine the efficacy and clinical factors related to the pharmacodynamics of single or combination therapies of valproic acid (VPA), carbamazepine (CBZ), and oxcarbazepine (OXC). Methods: The study evaluated the records of 2027 outpatients in a Changsha hospital, China, from December 23, 2015, to October 28, 2019. The baseline seizure frequency was assessed during the first visit. AED efficacy was determined based on the reduction in seizures from baseline at the subsequent visits. Multivariable ordinal regression analysis was used to determine the association between the clinical factors (demographic characteristics, clinical features, and medication situation) and AED efficacy. For validation, the clinical efficacies of AEDs were compared as both single agents and in combinations. Differences in adverse effect (AEs) categories were analyzed by Chi-square between AED groups. Results: Records of patients receiving VPA, CBZ, and OXC were evaluated. Serum concentrations of VPA and CBZ is significantly correlated with efficacy (OR 1.030[1.024-1.037], p ＜0 .0001; OR 1.250 [1.146-1.63], p < 0.0001, respectively) and OXC efficacy correlated to the serum concentration of the metabolite 10,11-dihydro-10-hydroxy-carbazepine (monohydroxy derivative, MHD) serum concentrations (OR 1.060 [1.031-1.089], p ＜ 0.0001). Significant differences existed between females and males in VPA efficacy (OR 1.318[1.033-1.682], p=0.027). After validation, VPA, in combination with OXC (OR 1.93[1.38-2.70], p＜0.001), or with VGB (Vigabatrin) (OR 2.36[1.38-2.70], p=0.002), showed significantly better efficacy than as a single agent. OXC efficacy was also affected by the duration of epilepsy (OR 0.965 [0.946-0.984], p ＜ 0.001). Additionally, the efficacies of OXC and VPA were also affected by the seizure type. Seizure reduction improved significantly with an increasing number of pharmacists’ educations in the first three visits period. Conclusion: Serum concentrations of VPA and CBZ may positively affect their efficacies, while OXC efficacies are correlated to MHD serum concentrations. The efficacy of VPA was higher in females compared to males. VPA-OXC and VPA-VGB combinations had higher efficacies compared to monotherapy. Besides, OXC efficacy is probably reducing by the duration of epilepsy. Additionally, VPA efficacy for focal or generalized seizures is superior to mixed-type seizures. OXC was more effective for focal seizures compared to mixed-type ones.